2021
DOI: 10.1186/s12936-020-03574-1
|View full text |Cite|
|
Sign up to set email alerts
|

Culturable bacteria associated with Anopheles darlingi and their paratransgenesis potential

Abstract: Background Malaria remains a major public health problem in South America, mostly in the Amazon region. Among newly proposed ways of controlling malaria transmission to humans, paratransgenesis is a promising alternative. Paratransgenesis aims to inhibit the development of parasites within the vector through the action of genetically modified bacteria. The first step towards successful paratransgenesis in the Amazon is the identification of Anopheles darlingi symbiotic bacteria, which are trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…It is efficient, cost effective, and minimally invasive compared to feeding and/or injecting synthetic antagomirs, and as such, this approach serves as an efficacious alternative to investigate microRNA related functions in the tsetse fly gut. This strategy can similarly be employed in any arthropod that houses genetically modifiable commensal gut symbionts that reside within host cells [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is efficient, cost effective, and minimally invasive compared to feeding and/or injecting synthetic antagomirs, and as such, this approach serves as an efficacious alternative to investigate microRNA related functions in the tsetse fly gut. This strategy can similarly be employed in any arthropod that houses genetically modifiable commensal gut symbionts that reside within host cells [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…et al [53] considered that" paratransgenesis" could be a promising alternative for controlling malaria transmission by Anopheles darlingi in the Amazon region. "Paratransgenesis aims to inhibit the development of parasites within the vector through the action of genetically modified bacteria".…”
Section: Rochamentioning
confidence: 99%
“…However, several bacterial isolates have been consistently detected in breeding sites, mosquito gut, and other mosquito-associated sources (Guégan et al, 2018). This is the case with Klebsiella, a genus of bacteria frequently reported in mosquitoes and their breeding sites (Gusmão et al, 2010;Chandel et al, 2013;Dada et al, 2014;Yadav et al, 2015;Wang et al, 2018;Hery et al, 2020;Alvarado et al, 2021;Rocha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have identified Klebsiella associated with Aedes , Anopheles , and Culex mosquitoes using both culture-dependent and independent methods ( Chandel et al, 2013 ; Yadav et al, 2015 ; Rocha et al, 2021 ). Therefore, it seems that these enteric bacteria maintain a stable relationship with the insects.…”
Section: Introductionmentioning
confidence: 99%